Influence of «Melanizol» and «Klimedeks» pessaries on phagocytic activity of polymorphonuclear leukocytes in vitro - O. V. Dolzhykova; L. M. Maloshtan (Фармацевтичний журнал, 2019)
Local immunity during aerobic vaginitis is provided by the functioning of the mucous membranes, the secretory immune system and cells that have the ability to phagocytosis. Neutrophils related to polymorphonuclear leukocytes (PNL), involved in phagocytosis reactions, are markers of inflammation and prevail in the vagina of patients with an infection.